2014
DOI: 10.1021/ef500743t
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of TBHQ Individually and Mixed with BHT in Petroleum Products Using a Gold Disc Electrode

Abstract: A new method is proposed for determination of TBHQ (tert-butylhydroquinone) individually and in a mixture with BHT (butylated hydroxytoluene) in mineral oil and biodiesel when using linear-sweep voltammetry in combination with a gold disc electrode. Both of these analytes gave rise to the respective anodic peak in the supporting electrolyte based on a mixture of dilute H 2 SO 4 and isopropanol. The samples of mineral oil were extracted using ethanol, and the samples of biodiesel were analyzed without any speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Caramit et al (2015), Tomášková et al (2013), Chýlková et al (2015), Freitas and Fatibello-Filho (2010), and Medeiros, Rocha-Filho, and Fatibello-Filho (2010) have shown that the type of working electrode and voltammetric method chosen are important for the simultaneous determination of antioxidants. Hence, the working electrode and voltammetric method were selected for the simultaneous determination of dinonyl diphenylamine and butylated hydroxytoluene.…”
Section: Resultsmentioning
confidence: 99%
“…Caramit et al (2015), Tomášková et al (2013), Chýlková et al (2015), Freitas and Fatibello-Filho (2010), and Medeiros, Rocha-Filho, and Fatibello-Filho (2010) have shown that the type of working electrode and voltammetric method chosen are important for the simultaneous determination of antioxidants. Hence, the working electrode and voltammetric method were selected for the simultaneous determination of dinonyl diphenylamine and butylated hydroxytoluene.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research [16], we found, that direct analysis of the oils containing AOs is impossible due to the coverage of the working surface of the indicative electrode by the matrix. Thus, the extraction is a necessary step before the analysis.…”
Section: Quantitative Analysis Of 2-tert-butylphenol In Oil Samplesmentioning
confidence: 97%
“…As we described in our previous papers, e.g. [14][15][16][17][18][19], electrochemical techniques, especially voltammetry in combination with solid electrodes, represent simple, timeand costs-saving approach for determination of AOs even in mixtures or in samples with complicated matrices like mineral and synthetic oils or biofuels. Voltammetric behavior of 2-TBF and simple method for its determination are for the irst time described in the present paper.…”
Section: U N C O R R E C T E D P R O O F Introductionmentioning
confidence: 99%
“…It has been proven that the use of derivative techniques in these situations can be helpful for quantitative determinations because depending on the order of derivatization, they allow the linear or higher-order interference of the background, noise, and other interferents to be removed and the signal sensitivity and the resolution power to be increased. [20,[46][47][48][49][50] Deviation from bilinearity in the overlapped voltammetric signals restricts the use of most chemometrics methods to voltammetric measurements on a few particular systems which ensure linear behavior because these methods are specially developed for linear data analyses. Artificial neural networks (ANNs), due to their ability to model both linear and non-linear relationships between dependent and independent variables, are being used increasingly in electroanalytical determinations.…”
Section: Introductionmentioning
confidence: 99%
“…A problem arising in the application of linear sweep voltammetry for the simultaneous determination of multiple species, that influences the bilinearity of the voltammograms and the accuracy of the analytical quantification, is the effect of the background interference on the shape of the voltammogram for the latter components that is itself affected by the presence and the concentration of the former electroactive species, [45] which finally distorts the observed voltammograms due to the overlapping of the voltammetric signals. It has been proven that the use of derivative techniques in these situations can be helpful for quantitative determinations because depending on the order of derivatization, they allow the linear or higher‐order interference of the background, noise, and other interferents to be removed and the signal sensitivity and the resolution power to be increased [20,46–50] . Deviation from bilinearity in the overlapped voltammetric signals restricts the use of most chemometrics methods to voltammetric measurements on a few particular systems which ensure linear behavior because these methods are specially developed for linear data analyses.…”
Section: Introductionmentioning
confidence: 99%